No Scientific Discipline Was Ever Built on a Myth. - Wegner, Peter; Guntheroth, Kurt; Stern, Joshua; Marks, David; Denning, Peter J. (Communications of the ACM, 2004)
This article presents several letters to the editor that pertain to the following: Information on software programming, information on the differences between the branch of computer science and software engineering, and the necessity of improving the educational curricula related to software engineering.